Practice Patterns in the Care of Acute Achilles Tendon Ruptures: Is There an Association with Level I Evidence?. Issue 7 (18th July 2016) - Sheth, Ujash; Wasserstein, David; Moineddin, Rahim; Jenkinson, Richard; Kreder, Hans; Jaglal, Susan
Objectives: Over the last decade, there has been a growing body of level I evidence supporting non-operative management (focused on early range of motion and weight bearing) of acute Achilles tendon ruptures. Despite this emerging evidence, there have been very few studies evaluating its uptake. Our primary objective was to determine whether the findings from a landmark trial assessing the optimal management strategy for acute Achilles tendon ruptures influenced the practice patterns of orthopaedic surgeons in Ontario, Canada over a 12-year time period. As a second objective we examined whether patient and provider predictors of surgical repair utilization differed before and after dissemination of the landmark trial results. Methods: Using provincial health administrative databases, we identified Ontario residents ≥ 18 years of age with an acute Achilles tendon rupture from April 2002 to March 2014. The proportion of surgically repaired ruptures was calculated for each calendar quarter and year. A time series analysis using an interventional autoregressive integrated moving average (ARIMA) model was used to determine whether changes in the proportion of surgically repaired ruptures were chronologically related to the dissemination of results from a landmark trial by Willits et al. (first quarter, 2009). Spline regression was then used to independently identify critical time-points of change in the surgical repair rate to confirm our findings. A multivariate logistic regression model was used to assess for differences in patient (baseline demographics) and provider (hospital type) predictors of surgical repair utilization before and after the landmark trial. Results: In 2002, ˜19% of acute Achilles tendon ruptures in Ontario were surgically repaired, however, by 2014 only 6.5% were treated operatively. A statistically significant decrease in the rate of surgical repair (p < 0.001) was observed after the results from a landmark trial were presented at a major North American conference (February 2009). Prior to the dissemination of trial results, the odds of undergoing surgical repair at a teaching hospital were found to be significantly higher than if treated at a non-teaching hospital (odds ratio (OR), 1.52; 95% confidence interval (CI), 1.04-2.22; p = 0.03). However, after the landmark trial there was no significant difference in the odds of undergoing surgical repair between teaching and non-teaching hospitals (p = 0.46). All other predictors of surgical repair utilization remained unchanged in the before-and-after analysis. Conclusion: The current study demonstrates that large, well-designed randomized trials, such as the one conducted by Willits et al. can significantly change the practice patterns of orthopaedic surgeons. Moreover, the significant decline in surgical repair rate at both teaching and non-teaching hospitals after the landmark trial suggests both academic and non-academic surgeons readily incorporate high quality evidence in to their practice.